2017
DOI: 10.1093/qjmed/hcx076
|View full text |Cite
|
Sign up to set email alerts
|

Codeine use, dependence and help-seeking behaviour in the UK and Ireland: an online cross-sectional survey

Abstract: . Codeine use, dependence and help-seeking behaviour in the UK and Ireland: an online cross-sectional survey. QJM, 110(9), 559-564. https://doi.org/10.1093/qjmed/hcx076Citing this paper Please note that where the full-text provided on King's Research Portal is the Author Accepted Manuscript or Post-Print version this may differ from the final Published version. If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 24 publications
2
34
0
Order By: Relevance
“…The study identified a population engaging in complex substance use of a relatively young age (mean age = 34.9 years) where specific challenges in terms of identification, intervention, and treatment exist. The findings of the study add to previous studies to underline the potential for misuse and dependence of codeine where use of prescribed and over-the-counter products for genuine medical reasons transitions into problematic use (Cooper, 2013;Kimergård et al, 2017;Van Hout et al, 2015). However, our findings also describe codeine use for recreational purposes where high doses are consumed to induce opioid euphoria.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…The study identified a population engaging in complex substance use of a relatively young age (mean age = 34.9 years) where specific challenges in terms of identification, intervention, and treatment exist. The findings of the study add to previous studies to underline the potential for misuse and dependence of codeine where use of prescribed and over-the-counter products for genuine medical reasons transitions into problematic use (Cooper, 2013;Kimergård et al, 2017;Van Hout et al, 2015). However, our findings also describe codeine use for recreational purposes where high doses are consumed to induce opioid euphoria.…”
Section: Discussionsupporting
confidence: 73%
“…The degree of psychological dependence on codeine was measured using the Severity of Dependence Scale. The scale has previously been used to assess codeine dependence (Kimergård et al, ; Nielsen, Cameron, & Lee, ). The scale is easy to administer due to its brevity and consists of five questions scored from 0 to 3 for a total score between 0 and 15.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Poland, the main reasons explaining the increasing misuse of NPDs were the availability of information on drugs on the Internet and the free access to these drugs . So, measures contributing to restrict their access should reduce these drugs' misuse, even without suppressing the problem as codeine dependence was evidenced with both prescribed and nonprescription codeine …”
Section: Discussionmentioning
confidence: 99%